Is circulating survivin altered in acromegaly? - Esra Ademoglu (Medicine Science, 2018)
Acromegaly is a chronic disorder which is characterized by growth hormone (GH) excess. In most of cases, GH hypersecretion is derived from somatotroph cell tumors. Survivin is a member of apoptosis protein family, which was recently showed to be expressed in tissue samples of different benign and malignant human tumors. This study is intended to determine circulating levels of survivin in newly diagnosed acromegaly patients with somatotroph adenomas. 19 newly diagnosed acromegaly patients with somatotroph adenomas were inclu-ded in the study. Concurrently, 19 healthy individuals were included as control group. Serum survivin levels, GH, insulin like growth factor-1 (IGF-1) and, some other biochemical parame-ters as fasting glucose, creatinine, alanine aminotransferase, cholesterol, triglyceride, high den-sity lipoprotein cholesterol, low density lipoprotein cholesterol were measured in each subject. Correlation analysis was performed between survivin and GH, IGF-1. Serum survivin levels tended to be higher in acromegaly group, but this was not reach statistical significance (p>0.05). Serum survivin levels were comparable among acromegaly patients and controls. Neither GH nor IGF-1 correlated with serum survivin. Larger scale studies are needed concerning the circulating levels of survivin in patients with acromegaly. [Med-Science 2018; 7(2.000): 265-8]